2018
DOI: 10.1016/j.jtho.2018.10.042
|View full text |Cite
|
Sign up to set email alerts
|

P018 Afatinib Named Patient Use Program in Advanced NSCLC with Progression on Prior Therapy: Experience from Asian Centers

Abstract: Background: Cyber Knife robotic stereotactic radiosurgery is minimally invasive tumor treatment modality that can deliver high precision radiotherapy to any part of the body with minimal exposure to adjacent and surrounding vital organs and is used to treat oligometastasis of the lung from primary breast cancer patients. In the modern high precision treatment delivery, utmost care should be taken for motion management of tumor targets. The Objective of this study was to investigate the accuracy and efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Studies that reported on the prognostic impact of Exon 20ins varied significantly with regards to the genotypes compared, line and type of therapy received, and patient ethnicity. The majority of studies were retrospective chart reviews (n = 10), with three exceptions: one post-hoc analysis of trial data (LUX-Lung 2, LUX-Lung 3, and LUX-Lung 6) [ 21 ] and two prospective registries [ 23 , 24 ]. Most studies were conducted in Asia (n = 8), with the remainder in the US (n = 3), Europe (n = 1), and Latin America (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that reported on the prognostic impact of Exon 20ins varied significantly with regards to the genotypes compared, line and type of therapy received, and patient ethnicity. The majority of studies were retrospective chart reviews (n = 10), with three exceptions: one post-hoc analysis of trial data (LUX-Lung 2, LUX-Lung 3, and LUX-Lung 6) [ 21 ] and two prospective registries [ 23 , 24 ]. Most studies were conducted in Asia (n = 8), with the remainder in the US (n = 3), Europe (n = 1), and Latin America (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…No comparative studies were identified, but rather, nine single-arm phase I/II trials (range 11-115 patients) [40, 42, 43, 45-47, 49, 52, 53] two prospective cohort studies (29 and 35 patients) [23,29,39], two pooled analyses of clinical trials (21 and 23 patients) [21,48], and 22 retrospective observational studies (range 15-165 patients). Half of the studies (n = 16) reported on subgroups or select cohorts of patients with Exon 20ins from studies with broader PLOS ONE PLOS ONE study populations, and half were conducted in Asia (n = 14), followed by the US (n = 8).…”
Section: Clinical Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORR in the current analysis was 43% (3/7 patients), compared with 30% (8/27 patients) in the global NPU analysis [4]. The difference in median TTF between patients with G719X, L861Q, or S768I mutations in the Asian subgroup and the global NPU program may have been particularly influenced by the median of 21.1 months among patients from Taiwan [12], who were not included in the global NPU analysis [4]. However, the prolonged outcomes reported here for patients with G719X, L861Q, or S768I mutations are in agreement with data from the LUX-Lung 2, 3, and 6 studies; for patients with G719X, L861Q or S768I, ORR ranged from 56 to 100%, median PFS 8-15 months, and median OS was 17 months-not estimated.…”
Section: Discussionmentioning
confidence: 55%
“…This is an important finding as, without evidence, it cannot be assumed that patients from Asia respond similarly to those from other regions. However, median TTF for EGFR mutation-positive [12]. When the NPU program began, investigators/clinicians in Taiwan had already gained experience in the use of afatinib, through their involvement in phase I and II trials.…”
Section: Discussionmentioning
confidence: 99%